2002
DOI: 10.1017/s1366728902000226
|View full text |Cite
|
Sign up to set email alerts
|

Is there primacy of aspect in child L2 English?

Abstract: accounts for the acquisition of tense-aspect morphology in child L2 English. The main question addressed is whether early uses of tense-aspect in¯ections can be analyzed as a spell-out of semantic/aspectual features of verbs (such as punctuality, telicity, durativity, etc.). The data are drawn from a detailed longitudinal study of an eight-year-old Russian-speaking child who was acquiring English as L2 in the USA. It is ®rst shown that the emergence of tense-aspect morphology patterns by aspectual verb class. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
58
1

Year Published

2007
2007
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(64 citation statements)
references
References 34 publications
(47 reference statements)
5
58
1
Order By: Relevance
“…Therefore, although it may still be claimed that progressive marking is initially associated with durative verbs, the association is stronger with accomplishment verbs than with activity verbs in the earliest stage. This finding appears to contradict the developmental component of the AH confirmed by previous studies (e.g., Rocca 2002;Gavruseva 2002), according to which -ing is associated with activity verbs at early stages and spreads to other nonprototypical verbs at later stages. However, the finding is in line with a number of studies that have shown that the association of activities with the progressive is not necessarily stronger at the lower levels of proficiency (e.g., Robison 1995;Bardovi-Harlig & Bergström 1996;Bardovi-Harlig 1998;Clachar 2004).…”
Section: Discussioncontrasting
confidence: 83%
See 2 more Smart Citations
“…Therefore, although it may still be claimed that progressive marking is initially associated with durative verbs, the association is stronger with accomplishment verbs than with activity verbs in the earliest stage. This finding appears to contradict the developmental component of the AH confirmed by previous studies (e.g., Rocca 2002;Gavruseva 2002), according to which -ing is associated with activity verbs at early stages and spreads to other nonprototypical verbs at later stages. However, the finding is in line with a number of studies that have shown that the association of activities with the progressive is not necessarily stronger at the lower levels of proficiency (e.g., Robison 1995;Bardovi-Harlig & Bergström 1996;Bardovi-Harlig 1998;Clachar 2004).…”
Section: Discussioncontrasting
confidence: 83%
“…A series of studies have reported similar findings on the acquisition of the English tense and aspect system by children (Rhode 1996;Gavruseva 2002) uninstructed adult learners in an ESL context (Robison 1990;Bardovi-Harlig and Bergström 1996), and instructed EFL and ESL learners (Bardovi-Harlig 1992;Robison 1995;Bardovi-Harlig and Reynolds 1995;Housen 2002;Collins 2002Collins , 2004Ayoun and Salaberry 2008).…”
Section: Evidence About the Acquisition Of The Progressive In Englishmentioning
confidence: 75%
See 1 more Smart Citation
“…Numerous studies have shown that child English L2 learners also display variable use of tense morphemes in their interlanguage (Dulay & Burt, 1973, 1974Gavruseva, 2002Gavruseva, , 2004Haznedar, 2001;Haznedar & Schwartz, 1997;Ionin & Wexler, 2002;Jia & Fuse, 2007;Lakshmanan, 1994;Paradis, 2005). The more particular question for our purposes is whether they show the (E)OI patterns as described above in their use of optional infinitives.…”
Section: Optional Infinitives and L2 Theoretical Accountsmentioning
confidence: 99%
“…Lardiere states in a footnote (p. 136) that ' Robison (1995) is an exception in that he looked at the use of verbal morphology across other temporal contexts (such as present and future) as well', but Bardovi-Harlig's (1999) list of AH studies include many more exceptions: Housen (1993; on Dutch; Robison (1990), Rohde (1996) on English, Shirai and Kurono (1998: Study 1) on Japanese; Andersen (1991) on Spanish. There are more recent studies on English: Bayley, 1999;Lee, 2001;Gavruseva, 2002;Housen, 2002;Rohde, 2002. It is important to point out that only one of these studies (Rohde, 2002) reports an obligatory context analysis, and that it does not restrict the analysis to obligatory contexts (i.e.…”
Section: Obligatory Context Analysis and The Aspect Hypothesismentioning
confidence: 99%